Comorbidity of TMD and malocclusion - Beatriz Moraes D'Avilla; Michelle Cristina Berbet Pimenta; Vivian Fernades Furletti; Mario Vedovello Filho; Giovana Cherubini Venezian; William Custodio (Universidade Estadual de Campinas, 2019)
Aim: to evaluate the synergic impact of muscular TMD and malocclusion on quality of life, masticatory capacity and emotional features of young adults. Methods: this cross-sectional study comprised 4 groups (n= 15): G1, individuals without TMD or malocclusion; G2, with TMD and malocclusion; G3, with TMD and without malocclusion, and G4, without TMD and with malocclusion. Muscular TMD was diagnosed by RCD/TMD. Data included quality of life (OHIP-14), masticatory capacity test (X50), emotional stress (PSS-14), depression (MDI), pain intensity and salivary cortisol. Comparative statistical analysis included One-way ANOVA and Tukey post hoc test (X50, stress and cortisol) and GENMOD followed by Wald test (OHIP-14 and pain data). Fisher's and Pearson's association analysis were carried out. Results: Comorbidity of muscular TMD and malocclusion leads to significant lower masticatory capacity (p<0.05). TMD groups independently of the occlusal condition had considerably lower OHIP-14 scores and higher stress levels (self-perceived and hormonal) (p<0.05).  There was no statistically significant difference of emotional depression among groups. A significant positive correlation was observed among quality of life, stress and pain perception. Conclusion: muscular TMD in the overlap of malocclusion potentializes their negative effect on masticatory capacity. In addition, the hindering effect of the comorbidity is variable, however, TMD has a greater negative impact on quality of life and stress, whilst malocclusion on mastication.